PENGARUH PEMBERIAN PENGUATAN TERHADAP HASIL BELAJAR MAPEL SOSIOLOGI KELAS X IPS SMAN 6 PONTIANAK - Mery Megawati; Rustiyarso Rustiyarso; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract The purpose of this study is to find out (1) how the reinforcement made by the teacher in the sociology subjects of class X IPS in SMAN 6 Pontianak (2) How are the students' learning outcomes in sociology subjects in class X IPS in SMAN 6 Pontianak (3) Is there any influence provision of reinforcement of student learning outcomes in sociology subjects in class X IPS in SMAN 6 Pontianak (4) How much influence the reinforcement of student learning outcomes in sociology subjects in class X IPS in SMAN 6 Pontianak. This type of research is survey research. The population in this study were 119 students with a sample of 92 students. Data collection techniques used are using indirect communication techniques and documentaries. Based on the research data obtained, it is stated that there is an influence between giving reinforcement on student learning outcomes in sociology subjects in class X IPS in SMAN 6 Pontianak by 3.8% with a correlation coefficient of 0.220 with a low level of interpretation. Based on the SPSS output table in the attachment with the Model title Summary can be determined the value of the correlation coefficient influence between the provision of reinforcement of learning outcomes of 0.220 (R) with Adjusted R Square 0.038 which was determined to 3.8%, meaning the effect of reinforcement the learning outcomes by 3.8%. Keywords: Reinforcement, Learning Outcomes, High School Student